Global research trends in food security: Insights from a bibliometric analysis - Dg. Junaidah Awang Jambol; Mohamad Ikhram Mohamad Ridzuan; Mohd Waliuddin Mohd Razali; Nur Auni Ugong; Nurulasyikin Hassan; Noor Syakirah Zakaria; Azizan Morshidi; Zulayti Zakaria (RSIS International, 2025)
In light of escalating global challenges, including climate change, population growth, and economic disparities, food security has emerged as a critical area of research. This study presents a comprehensive bibliometric analysis of food security literature sourced from the Scopus and Web of Science (WoS) databases, encompassing 506 valid publications. The findings reveal a notable upward trend in scholarly interest over the past decade, with a particular focus on themes such as climate change, sustainability, agricultural innovations, and the socioeconomic dimensions of food systems. Significant contributions highlight the effectiveness of interdisciplinary approaches and regional research, especially in Southeast Asia, where Malaysian institutions have demonstrated notable leadership. Some important insights are the use of advanced modelling methods like hydrodynamic and socio-ecological frameworks, the integration of behavioural reasoning and generational cohort theories, and the wide use of farming methods that are resilient to climate change. The study also identifies highly cited works that address sustainable practices and policy implications, reflecting the multifaceted nature of the field. However, gaps remain in areas such as the impacts of microplastics, urban food deserts, and the role of blockchain technology in food systems. This research underscores the necessity for international collaboration and the adoption of multidisciplinary perspectives to advance sustainable solutions for food security. This bibliometric mapping serves as a strategic guide for researchers, policymakers, and stakeholders to address critical knowledge gaps and foster innovation in achieving global food security objectives.